Beginning C++ Game Programming Learn to Program with C++ by Building Fun Games - Horton, John (Packt Publishing, Limited., 2019)
This book is a fun introduction to the world of game programming, C++, and the OpenGL-powered SFML using five fun, fully playable games of increasing difficulty and advancing features.
Includes bibliographical references and index. - Online resource; title from PDF title page (viewed May 10, 2021)
Keywords: C++ (Computer program language); Video games -- Programming; C++ (Langage de programmation); Jeux vidéo; Programmation; Video games; Programming